Estação OO: um ambiente integrado de desenvolvimento para a introdução à programação orientada a objetos com java - Maria Vanderlea de Queiroz Alves (2005)
This work presents a study which analyzes microwords and the use of Integrated Development environments (IDEs), driven by didacticism and pedagogy. In the context of real classrooms, the study tried to verify how these features could contribute in the teaching/learning process. The main focus of the study is the introductory programming disciplines using the Java language and the object oriented programming approach. The work inquires on when pedagogical patterns, design patterns and coding patterns could be used by beginners and was based on suggestions from literature and some case studies, carried out to test the viability of these suggestions. This work also proposes a didactic framework, called "Estação OO", which make use of a metaphor for a "trip" in the form of a map or route to conduct the trainee in Object Orientation which gathers the most promising suggestions from studies and their adaptations available on literature. The proposal of Estação OO takes into account the apprentices difficulties demonstrated when they were using the tools studied. An additional IDE, based on BlueJ, incorporating ideas and procedures available on literature is outlined and suggested for use in introductory programming disciplines.